2019
DOI: 10.3389/fphar.2019.01429
|View full text |Cite
|
Sign up to set email alerts
|

UFR2709, a Nicotinic Acetylcholine Receptor Antagonist, Decreases Ethanol Intake in Alcohol-Preferring Rats

Abstract: Brain nicotinic acetylcholine receptors (nAChRs), a heterogeneous family of pentameric acetylcholine-gated cation channels, have been suggested as molecular targets for the treatment of alcohol abuse and dependence. Here, we examined the effect of the competitive nAChR antagonist UFR2709 on the alcohol consumption of high-alcohol-drinking UChB rats. UChB rats were given free access to ethanol for 24-h periods in a two-bottle free choice paradigm and their ethanol and water intake were measured. The animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Thus, our results indicate that UFR2709 produces a blockade of the effects of nicotine. In addition, we have recently reported the ability of UFR2709 to decrease ethanol intake in alcohol-preferring rats [40]. Therefore, our current and previous results indicate that this compound might serve to counteract the effects of a relatively wide spectra of addictive compounds and give further support to the notion that nAChR play a pivotal role in drug abuse [44].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Thus, our results indicate that UFR2709 produces a blockade of the effects of nicotine. In addition, we have recently reported the ability of UFR2709 to decrease ethanol intake in alcohol-preferring rats [40]. Therefore, our current and previous results indicate that this compound might serve to counteract the effects of a relatively wide spectra of addictive compounds and give further support to the notion that nAChR play a pivotal role in drug abuse [44].…”
Section: Discussionsupporting
confidence: 73%
“…Here, we report that both UFR2709 ( Figure 1), a nAChR antagonist that reduces ethanol intake in rats [40], and nicotine exert anxiolytic effects on zebrafish subjected to the novel tank diving test. Furthermore, we show that UFR2709 blocks the effect evoked by nicotine on the CPP paradigm and that both treatments differentially affect the levels of mRNA expression of α4 and α7 nACh receptor subunits in the brain of adult zebrafish.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…It was demonstrated that different nicotinic ligands can reduce ethanol ingestion in animal models and humans. [ 16 , 17 , 18 , 19 , 20 , 21 ]. The reward system or mesocorticolimbic system projects dopamine neurons from the ventral tegmental area (VTA) to the nucleus accumbens (NAc) and prefrontal cortex (PFC) [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we recently demonstrated, using UChB rats, that UFR2709, a competitive nicotinic antagonist [ 59 ], reduces voluntary ethanol intake in a dose-dependent manner without affecting body weight or locomotor activity, and does not produce a DA release from the striatum under i.p. injection [ 20 ]. In this work, we studied the effect of UFR2709 administration in the acquisition and the maintenance of ethanol intake in UChB rats that were chronically exposed to ethanol consumption.…”
Section: Introductionmentioning
confidence: 99%